Priesthood, Its Spirituality: The Philippine Experience - Lacal, Marlon A (Asian Horizons, 2009)
In the Philippines’ cultural milieu and context, the influences of the ordained ministers shaped and fashioned the church and its impact on society. Filipino priests propel the local church into a new evangelizing thrust and direction. They are always challenged to be attuned to the ebb and flow of the life and situation of the people and to be responsive to the signs of the times. They are in one way or another part of the structures and/or elements that helped make or break the culture, history and destiny of the people seeking and searching for their definitive destiny and future.